Deep Brain Stimulation of bilateral Subthalamic nucleus (STN) following pallidotomy with Parkinsons crisis: A case report - Shrestha, Resha; Shrestha, Pranaya; Rajbhandari, Pravesh; Acharya, Samir; Pant, Basant (Nepal Journal of Neuroscience, 2018)
We present a case of 57 years old patient with Idiopathic Parkinsons disease(PD) who had right sided Globus PallidusInternus (GPi) lesioning or pallidotomy as surgical treatment modality of PD. However this patient went into Parkinsons crisis postoperatively which is a rare form of complication. We had to admit in critical care for two weeks before he gradually improved and reached to preoperative state. This patient finally underwent deep brain stimulation(DBS) of bilateral Subthalamic nucleus (STN) and he has improved in terms of Unified Parkinson’s Disease Rating Scale(UPDRS) score.Nepal Journal of Neuroscience 15:40-42, 2018